Guilty By Reason of Insanity: Unforeseen Consequences of California's Deinstitutionalization Policy - Rushforth, Jen (2015)
Beginning with the passage of the Lanterman-Petris- Short Act in 1969, deinstitutionalization in California has had a devastating effect on the mentally ill. Instead of affording the mentally ill with more rights and protections, the process of shutting down state psychiatric hospitals and impeding psychiatric care for those in need caused a cascade effect leading to an increase of homelessness and incarceration. Over the past four decades, prisons and jails in California have become the de facto state mental hospitals, with severely mentally ill individuals having nearly a four-to-one chance of ending up in jail or prison over a psychiatric facility of some variety. This restructuring of mental health services has contributed to the ever-increasing problem of mass incarceration – a problem that has reached epidemic levels in recent years. To that end, solutions to this problem include: community-based mental health services, reopening some state psychiatric hospitals with greater oversight, funding medical research into improved treatment options, and community education aimed at fostering a greater understanding of mental health issues